PENGARUH KUALITAS PEELAYANAN TERHADAP NIAT BELI ULANG MELALUI KEPUASAN PADA SWALAYAN KPD DI PALANGKA RAYA - Ari Gunawan; Yunikewaty Yunikewaty; Meitiana Meitiana (Media Bina Ilmiah, 2023)
Research in the field of marketing with the aim of this study is to measure and analyze the effect of service quality on repurchase intentions at KPD Swalayan Palangka Raya. Measuring and analyzing the effect of satisfaction on repurchase intention at KPD Swalayan Palangka Raya. Measuring and analyzing the effect of Service Quality on Satisfaction at KPD Swalayan Palangka Raya. Measuring and analyzing the effect of service quality on repurchase intention through satisfaction at KPD Swalayan Palangka Raya. The population in this study are consumers who shop at KPD Supermarkets in the City of Palangka Raya as many as 200 respondents. KPD Supermarket research location in Palangka Raya City. Primary and secondary data sources, data collection methods used observation, and distribution of questionnaires. The analytical tool used in this study is Smart-PLS Version 3.0. The results of this study indicate that service quality has a positive and significant effect on repurchase intentions. Consumer satisfaction has a positive and significant effect on repurchase intention. Service quality has a positive and significant effect on satisfaction. Service Quality on Repurchase Intentions through satisfaction has a positive and significant effect.